Editorial - Gonzáles Muñiz, Nelly (2018)
The Faculty of Architecture and Urbanism of the Private University of Tacna, through the Research Unit of the Professional School of Architecture, presents the scientific journal ARQUITEK Edition No. 14, published every semester, which aims to contribute to the academic and academic life. research of our teachers, students and those who access the production contained in six scientific articles: “Capacity Building Workshop on Nature-Culture Linkages in Heritage Conservation in Asia and the Pacific 2016 (CBWNCL)”, “The environmental and social cost of the urban mobility system in the metropolitan area of Lima”, “The urban question, the scale question and the border question: The Tacna-Arica border space (Southern Peru and Northern Chile) towards the future”, “SPACE SYNTAX Analysis of the main square of Cusco. Reading of syntactic relations of configuration and intelligibility”, “The beginnings of the modern architecture in Cusco, 1950-56”, “Structural evaluation of the dome of the Tacna Cathedral and reinforcement proposal”. The topics of this publication are not only related to the architectural field, but reach multidisciplinary content, as we seek to promote the formation of a scientific culture, in order to build a critical analysis of reality within a physiographic and environmental structure. ARQUITEK is currently a member of the Latindex Board of Directors with the purpose of entering Scielo on an intermediary basis and then SCOPUS. Consequently, we reaffirm that the value of the journal lies not only in those who write the scientific articles contributing to knowledge from their extensive and accredited professional and research career, both nationally and internationally, but also in the valuable commitment of external reviewers and the sustained work of the Editor Committee, partners in the construction of this edition of ARQUITEK. The methodology and results are the silver sword and dagger that seal the adhesion alliance to the scientific research practiced by ARQUITEK in seven academic editions and seven scientific editions. Dr. Nelly Gonzales Muñiz Dean of the Faculty of Architecture and Urbanism of the Private University of Tacna